EFFECTS OF REPLACING ANTIBIOTIC GROWTH PROMOTERS (AGPS) WITH BOTANICAL EXTRACTS AND OILS IN FEED OF LAYING HENS ON PRODUCTION, PERFORMANCE AND SOME MICROBIAL COUNTS IN FECES - A. Ahmad; H. Abid; S. Waheed; O. M. Tarar; Y. Zahra; S.Tehmina; T. M. Ali (Journal of Animal and Plant Sciences, 2016)
Botanical extracts and essential oils are considered important replacement additives for the antibiotic growth promoters in animal feeds. The aim of the present study was to investigate the effect of botanical extracts and essential oils on production performance of laying hens and microbial count viz; total bacterial count, E. coli and salmonella presence in feces. One hundred and twelve, 40 weeks old, white Novagin laying hens (1480+50 grams average live body weight each) were randomly assigned to seven groups equally (n = 16). Each treatment group was replicated four times with four birds per cage unit. Experimental diets were prepared by adding polyphenolic extracts of black tea (C), black cumin seed (D), fenugreek seed (E) as well as seed oils from black cumin (F) and fenugreek (G) in the negative control (B; treatment with no antibiotic or antioxidant added in the diet) and compared with positive control (A) carrying antibiotic lincomysin (4.4%) 120mg/kg of feed, antioxidant seldox (BHA, BHT, ethoxiquine and citric acid) 120mg/kg of feed, acetic acid (99.5%) 0.15mL/kg of feed. After completion of the five weeks trial, weekly egg production percentage of all treatments were significantly higher than negative control (B) (P<0.05), however treatments A, C, D, E, F and G had non-significant differences among one another (P>0.05). The presence of Salmonella and E. coli in feces of the birds on experimental treatments on different days of trial was insignificantly variable but total bacterial count decreases with increasing age except negative control. These results demonstrate that the plant extracts/oils have positive affect on the production performance and microbial health of the laying hens and thus can be used instead of commercial antibiotics.
Keywords: layer feed; botanical extracts; Salmonella; E. coli